2011
DOI: 10.2147/ijn.s26051
|View full text |Cite
|
Sign up to set email alerts
|

Translocation of PEGylated quantum dots across rat alveolar epithelial cell monolayers

Abstract: Background: In this study, primary rat alveolar epithelial cell monolayers (RAECM) were used to investigate transalveolar epithelial quantum dot trafficking rates and underlying transport mechanisms. Methods: Trafficking rates of quantum dots (PEGylated CdSe/ZnS, core size 5.3 nm, hydrodynamic size 25 nm) in the apical-to-basolateral direction across RAECM were determined. Changes in bioelectric properties (ie, transmonolayer resistance and equivalent active ion transport rate) of RAECM in the presence or abse… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 55 publications
(78 reference statements)
0
8
0
Order By: Relevance
“…When Yacobi et al [23] applied the same experimental approach, it was found that translocation of both positively and negatively charged PNP across RAECM takes place predominantly via non-endocytic transcellular pathways. We also recently showed that PEGylated quantum dots (core size ~5 nm, hydrodynamic size ~25 nm, amine-, carboxylate- and non-modified) can traverse EGTA-disrupted tight junctions [29]. …”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…When Yacobi et al [23] applied the same experimental approach, it was found that translocation of both positively and negatively charged PNP across RAECM takes place predominantly via non-endocytic transcellular pathways. We also recently showed that PEGylated quantum dots (core size ~5 nm, hydrodynamic size ~25 nm, amine-, carboxylate- and non-modified) can traverse EGTA-disrupted tight junctions [29]. …”
Section: Discussionmentioning
confidence: 99%
“…The most abundant proteins found in clathrin-coated pits are clathrin and the heterotetrameric adaptor protein 2 (AP-2) [44]. Chlorpromazine causes clathrin and AP-2 to relocate to multivesicular bodies, causing inhibition of clathrin-mediated endocytosis [23, 29]. Treatment of MAECM with 28 µM chlorpromazine in this study led to ~60–80% decrease in trafficking of amidine-modified (positively charged, 20 and 120 nm) but not carboxylate-modified (negatively charged, 20 and 100 nm) PNP (Figure 3), consistent with the notion that positively (but not negatively) charged NP preferentially associate with clathrin-coated pits and are subsequently taken up into/translocated across certain (but not all) epithelial barriers.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Therefore, uptake of charged particles can be cell specific, and our platform provides data about how the respiratory airway epithelium responds to inhaled nanoparticles. While there is data in the lower alveolar epithelium (Fazlollahi et al 2011; Fazlollahi et al, 2011; Kim et al 2010; Yacobi et al 2008, 2009, 2007), the airway epithelium has a higher paracellular permeability (Widdicombe J 1997), and transport could be substantially altered. The mechanisms dictating these routes are unknown.…”
Section: Resultsmentioning
confidence: 99%
“…Of note, it has been calculated that the airway epithelial barrier is more permeable than the alveolar barrier (Widdicombe J 1997), and therefore mechanisms of transport could be of great significance in airway epithelial cells. Studies have shown that charged particles can traverse the alveolar epithelium, primarily transcellularly (Fazlollahi et al 2011; Fazlollahi et al, 2011; Kim et al 2010; Yacobi et al 2008, 2009, 2007). Published studies, such as those by Yacobi et al(Yacobi et al 2009) have considered nanoparticle transport through the alveolar epithelium, and have shown that both positively and negatively charged particles traverse transcellularly, though at different rates.…”
Section: Discussionmentioning
confidence: 99%